2008
DOI: 10.1002/mrm.21482
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive PARACEST contrast agent for temperature MRI: Eu3+‐DOTAM‐glycine (Gly)‐phenylalanine (Phe)

Abstract: Tissue temperature is a fundamental physiological parameter that can provide insight into pathological processes. The purpose of this study was to develop and characterize a novel paramagnetic chemical exchange saturation transfer (CEST) agent suitable for in vivo temperature mapping at 9.4T. The CEST properties of the europium (Eu 3؉ ) complex of the DOTAMGlycine (Gly)-Phenylalanine (Phe) ligand were studied in vitro at 9.4T as a function of temperature, pH, and agent concentration. The transfer of magnetizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
110
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 29 publications
2
110
0
Order By: Relevance
“…Our previous study showed that a 5-mM concentration of the PARACEST agent Eu 3ϩ -DOATM-Gly-phenylalanine was necessary to generate a clear CEST contrast of ϳ2% in brain tissue or tissuelike samples (17). The sensitivity of both PARACEST and OPARACHEE methods will vary in different tissue types due to the MT effects from endogenous macromolecules (23,38).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study showed that a 5-mM concentration of the PARACEST agent Eu 3ϩ -DOATM-Gly-phenylalanine was necessary to generate a clear CEST contrast of ϳ2% in brain tissue or tissuelike samples (17). The sensitivity of both PARACEST and OPARACHEE methods will vary in different tissue types due to the MT effects from endogenous macromolecules (23,38).…”
Section: Resultsmentioning
confidence: 99%
“…The advantages of the OPARACHEE method compared to the conventional PARACEST method are the greater sensitivity, low power requirements and consequently low specific absorption ratio, and the insensitivity of the method to the bound-water chemical shift. However, most applications of PARACEST agents are based on the measurement of the chemical shifts of bound protons and/or the detection of bound proton CEST contrast (13,16,17). The OPARACHEE method will likely find utility in the detection of targeted agent uptake into tissue.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations